Improving the Students’ English Speaking through Omegle Platform - Aida, Aidyl fahri; Didik Santoso (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study explored the improvement of English speaking skills among higher education EFL students through the use of Omegle, a real-time interactive platform. Twenty Indonesian higher education EFL students participated in a one-month intervention that integrated Omegle into structured classroom activities. Data were collected through observations, pre- and post-tests, and semi-structured interviews. Quantitative results showed a notable improvement in speaking performance, with mean scores increasing from 48.2 in the pre-test to 72.5 in the post-test (t = 13.9, df = 19). Qualitative findings indicated that students became more confident, expanded their vocabulary, and spoke more fluently during spontaneous online conversations. These findings highlighted how combining digital platforms with classroom instruction fostered measurable progress in language proficiency. The study suggested that interactive, technology-assisted practice provided authentic, low-pressure opportunities for developing speaking skills, while future research could examine longer- term interventions and larger, more diverse student populations.